A tradução pós-colonialista do romance Amada de Toni Morrison - Reis, Taís Marciele dos (2017)
In the world we live in, translation becomes very present and necessary for the identification and knowledge of subjects and cultures other than our own. Thus, the present work had as objective to identify the post-colonialist marks in the Brazilian translation made by José Rubens Siqueira of the work Amada written by the North American writer, Toni Morrison (2007), in addition, to explore the postcolonialist translation like form of transposition cultural and literary aspects of the diaspora and the constitution of the subject's identity. For that, some postcolonial theorists like Homi Bhabha (2014), Stuart Hall (1998), and the translation Susan Bassnett (1999), Lawrence Venuti (2002), Douglas Robinson (2002), André Levefere (2007) ). In addition, the postulates of the theorists and critics of the descriptive translation also serve as a beacon for this research, with the works, for example of the exponents Itamar Even-Zohar, creator of the theory of Polysystems (1990), by Gideon Toury, who coined the studies descriptions of the translation (2012). With this research it was possible to observe that the translation of José Rubens Siqueira was in its majority a neutral translation and that took in consideration the aspects of content that give postcolonial characteristics to the novel.